Implementation of Good Governence in the Jawa Village Office, Samarinda Ulu District in Government Administration - Ahmad Yani; Arnianti (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study was conducted to determine the application of the principle of responsiveness of good governance in public services at the Jawa district Office and to find out what the supporting and inhibiting factors are. This type of research is descriptive qualitative where data collection is carried out by library research and field research and using interactive model data analysis. The results showed that the application of the principle of responsiveness of good governance in public services at the Jawa Kelurahan office had been implemented by service officers but was not maximized because of the six indicators used in the study, there were indicators that had not been implemented properly, namely speed and timeliness in providing services. This is due to inadequate office work facilities and the lack of information reaching the public.